Situating emotionality within socialization in study abroad contexts: The Student's perspective. (June 2022) - Kim, Kyung Min
Abstract: Although second language emotion literature has emphasized the need to make emotionally difficult experiences transformative, the emotional realities of study abroad have remained almost in private narratives. By situating emotionality as one of the essential factors influencing students' socialization process (Duff, 2019 ) within a broader frame of study abroad, this case study traces a Chinese student's experience in a US university to see how emotionality maps onto his socialization process. To examine his poetic, linguistic, and academic identity, multiple sources of data were collected for three semesters: an interview, writing samples including autobiographical poems, and observation. The findings suggest that his affective stance shaped his engagement with English and multiple communities because it was intertwined with his investment within academic and non-academic venues. His stories illustrate how reframing his emotional struggles as investment allowed him to reinforce or negotiate his beliefs, learning strategies, and writer identity, thus revealing the nuanced ways in which his socially and emotionally mediated agency forged his multilingual identity. The study highlights the mediating role of reflection on emotionally charged experiences to lay a foundation for meaningful participation in new communities.